Crystal growth under microgravity condition - Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran; Leow, Adam Thean Chor (2008)
The present invention relates to the growth of protein crystallization on earth and in zero-gravity conditions. Moreover, the invention relates to preferred conditions to develop protein crystals or 3D crystal structures. Furthermore, the preferred embodiment of the present invention relates to an evaluation of 3D crystal growth under microgravity (zero-gravity) and on earth. In addition, the invention also relates to the quality of protein crystal/s grown on earth and zero-gravity. The present invention provides a new and improved method for growing protein crystals and for screening crystallization conditions in solution crystals growth.